The Ideal Concept towards the Welfare of Non-Livestock Animals in the Principle of Utilization and Utilization in Realizing Legal Certainty in Indonesia - Asmariah Asmariah (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Indonesia has Law No. 41 of 2014 and Government Regulation No. 95 of 2012 to support animal welfare, but the country is still ranked as "D" on the animal protection index. This low ranking is due to the fact that the welfare of non-livestock animals in Indonesia has not been fully realized in practice, which is caused by the lack of clarity and certainty regarding regulations that govern the principles of animal welfare in their use and utilization, as well as the criminal sanctions within them. An analysis is needed to determine the extent to which existing legal regulations and sanctions can accommodate the scope of animal welfare principles in the use and utilization of non-livestock animals and to formulate legal protections accordingly. The research problem is how to formulate an ideal concept of legal protection for non-livestock animals in their use and utilization as a guide to creating legal certainty. This research is a descriptive analytical study using a combined social normative-empirical research paradigm. The methodology of this research incorporates a model for the ideal formation of law, which includes the integration of three legal theories: Lawrence Meir Friedman's legal structure, legal substance, and legal culture; Mochtar Kusumaatmadja's Law as a tool of social engineering, which states that law is a social control tool; and Satjipto Rahardjo's assertion that the law is for humans, not the other way around. The ideal formation of law model is one solution to realize animal welfare